Introduction to selections from Akram Khan's Tafsirul Qur'an (Bangladesh Institute of Islamic Thought (BIIT), 2009)
At the dawn of the twenty-first century when Muslims in Bengal are still lagging behind other communities and are suffering from the loathsome syndrome of self-defeatism, a look back at the life and work of Mohammad Akram Khan (1868-1969) – popularly known as Maulana Akram Khan – may give rays of hope and bonfires of inspiration to the people at large, especially the Muslims, of this region. As is the case with Rokeya Sakhawat Hossain (1880-1932) and with many other Muslim luminaries of former Bengal, a research on Akram Khan gives us surprises and disbelief that this land could be the fertile ground of such great scholars and that their successors can be oblivious of their rich cultural and intellectual tradition to such an awful extent! When we find ourselves mesmerized by the seemingly superior achievements of other societies and communities both local and foreign – some of whom perhaps for reasons known to them cannot accept Muslims as equals – and engage ourselves in the vicious cycle of self-hatred, the legacy of Akram Khan and the like stares us in the face with a strong feeling of pity and commiseration. While our predecessors in the region left an indelible mark of devotion, selflessness, altruism, profound intellectualism and great scholarship, and above all, self-respect and confidence, we have indulged in flippancy, selfishness, insularity and narrowness, greed and avarice, conceit and narcissism, intellectual pretension, and the worst of all, a fatalistic tendency of self-defeat and self-hate. Studying great figures like Akram Khan may help us wake up from this confused slumber and intellectual disorientation, as it may augur the revival of the lost era of glory and confidence especially in the Muslim community.